2010
DOI: 10.1111/j.1467-9450.2010.00815.x
|View full text |Cite
|
Sign up to set email alerts
|

How health information affects college students’ inclination toward variety-seeking tendency

Abstract: College students often consume too much snacks (e.g. potato chips) and such high-fat snacks are found to be related to obesity. This paper seeks to explore the effect of health-related information on the relationship of mood states and variety seeking (VS) behavior among enjoyable snacks. Health warnings and nutritional labeling are used to examine the moderating effects on this relationship. Consistent with our hypotheses, the results indicate that the presence of health warnings attenuates the influence of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Additional specific psychological approaches that have demonstrated efficacy in treating anxiety in children and adolescents include: attention bias modification (ABM) [1226], MBCT [1195], and social effectiveness therapy (SET) [1227,1228] for SAD; ERP [1229,1230], family-based CBT [1231,1232], and meta-cognitive therapy [1229] for OCD; cognitive behavioral writing therapy (CBWT) [1233], spiritual-hypnosis assisted therapy (SHAT) [1234], emotion regulation therapy [1235], exposure therapy [1236], and EMDR [905,1237,1238] for PTSD; and exposure therapy for specific phobias [313]. …”
Section: Special Populationsmentioning
confidence: 99%
“…Additional specific psychological approaches that have demonstrated efficacy in treating anxiety in children and adolescents include: attention bias modification (ABM) [1226], MBCT [1195], and social effectiveness therapy (SET) [1227,1228] for SAD; ERP [1229,1230], family-based CBT [1231,1232], and meta-cognitive therapy [1229] for OCD; cognitive behavioral writing therapy (CBWT) [1233], spiritual-hypnosis assisted therapy (SHAT) [1234], emotion regulation therapy [1235], exposure therapy [1236], and EMDR [905,1237,1238] for PTSD; and exposure therapy for specific phobias [313]. …”
Section: Special Populationsmentioning
confidence: 99%
“…For example, a study with 124 subjects demonstrated that people are likely to include more variety in their consumption decisions when they are induced to a negative emotion than a positive emotion ( Chuang et al, 2008 ). Moreover, a series of research discussed the effect of two specific emotional states (sadness and happiness) on variety-seeking behaviors and found similar conclusions ( Lin and Lin, 2009 ; Chien-Huang and Hung-Chou, 2010 , 2012 ; Lin et al, 2011 ; Lin, 2014 ). These studies used choice task scenarios and revealed that participants with a sad mood selected more variety than those with a happy mood.…”
Section: Analysis and Resultsmentioning
confidence: 88%
“…Then, researchers discussed how specific emotions and physical conditions, including positive and negative emotions ( Chuang et al, 2008 ), sadness and happiness ( Lin and Lin, 2009 ; Chien-Huang and Hung-Chou, 2010 , 2012 ; Lin et al, 2011 ; Lin, 2014 ), local optimism and pessimism ( Yang and Urminsky, 2015 ), and winning-losing perception ( Chang et al, 2021 ), affect consumers’ decision-making behaviors when faced with multiple choices. In these moods and states, seeking variety helps people change their current status.…”
Section: Analysis and Resultsmentioning
confidence: 99%
See 1 more Smart Citation